HUBUNGAN POLA ASUH DENGAN STATUS GIZI ANAK BATITA DI KECAMATAN KURANJI KELURAHAN PASAR AMBACANG KOTA PADANG TAHUN 2004 - Fivi Melva Diana (Jurnal Kesehatan Masyarakat Andalas, 2006)
From the epidemiological study of nutritional problems (SMG) in west Sumatra by the year of 2002 that 28,5% under five years babies were suffered under nutrition (based on BB/U , -2 SD) and 5,4% of them were malnutrition. Meanwhile in the city of Padang, based on BPS susenas reports in 2002,that 8,54% less than three years babies were malnutrition.From the reports of Padang health Officials in 2002, the highest malnutrition prevalence was in Kuranji district, which were 5,63%. This study were conducted at Pasar Ambacang sub-district,in the district of Kuranji,city of Padang.The research Variables were motherhood patterns, nutritional status and mother’s characteristics (education,age, knowledge and job status). The used design was cross sectional study design. Data processed and analyzed using SPSS software with chi square statistical test. The result showed that there is no significant relationship between motherhood patterns with nutritional status based on mothers characteristics ( p > 0.05), and based on previous explanation we could summarize that motherhood patterns and nutritional status does not have significant relationship with mother’s characteristics. From this study we could conclude that there were a significant correlation between mothers job status with motherhood eating patterns of under three years babies, and we suggested to the mothers, eventhough they worked, the still have to maintain the quality of the motherhood times in order to enhance the nutritional status and growth.